Effect of weed management and phosphorus levels on yield and quality of indian mustard (Brassica juncea) - SHARMA, R P; SINGH, P; MALIWAL, P L (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during the winter seasons of 1998-99 and 1999-2000 on Vertisols of Udaipur, to study the effect of weed-management and phosphorous level on yield and quality of indian mustard (Brassica juncea L.) Czernj. & Cosson. All the weed-management practices significantly increased the yield attributes, yield and net returns over the control. Weed-management practices increased the seed yield of indian mustard by 54.4-80.7% over the weedy check (1.14 tonnes/ha). Under weed-management treatments, oxyfluorfenresulted in the highest seed yield (2.6 tonnes/ha) and was found significantly superior to the other treatments exceptpendimethalin. The highest net returns (Rs 19 765) were also observed under oxyfluorfen treatment. Progressive increase in P application from 0 to 17.6 kglha significantly increased the yield attributes and seed (1.43 to 2.01 tonnes/ha) and stover (4.36 to 5.76 tonnes/ha) yields as well as oil (39.40 to 41.75%) and protein (18.91 to 23.22%) content of indian mustard seed. Application of 17.6 kg P/ha increased the mean seed yield of indian mustard by 40.6% by mean net returns by Rs 6 505/ha over the control.